DAMPAK EKONOMI DAN POLITIK INDONESIA SETELAH MENJADI TUAN RUMAH ASIAN GAMES 2018 - Maharrani Sukma; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes how the Economic and Political Impacts that Indonesia got after hosting the 2018 Asian Games. This research is a qualitative research that uses document analysis method on data obtained from journals, books, newspapers, and internet sites to describe the issues raised. This study explains the economic and political impact of the organizers. The perspective used is the perspective of liberalism with a nation-state level analysis. The results of the study show that Indonesia as the host of the 2018 Asian Games experienced economic and political improvement after becoming the host. This is evidenced by the development of infrastructure with international standards, economic growth through investment, job creation and tourist spending. In addition, in terms of politics, Indonesia has the opportunity to show itself that it is able to organize the largest sporting event in Asia to international countries and increase Indonesia's prestige as the host.Keywords: Asian Games 2018, Economy, Politics, Indonesia